FractalCity: the city amid policies - Colombo, A. (2018)
The track Fractalcity aim to reflect and discuss about the relationship between forms of governance and public policies, particularly in urban contexts. This debate was structured in a two-fold register. On one side, as national and international debate point out - both in the academic and grey literature - urban governance is a polysemic topic, that can be framed as a theory, a concept, or as a tool for public policies. On the other side, fractal city reflects the growing complexity of societal challenges, in between urban development paths of economic competition and unequal redistribution of territorial resources. Within this context, public policies are called to face these challenges, by acting in different levels of governance and involving multi-actor systems. However, public policies often produce or simply support disarticulated, contradictory and paradoxical urban scenarios, configuring themselves as (un)sustainable. Starting from these assumptions, this track discusses the role of diversified forms of organizational innovation, the importance of creating window of democratic opportunity and finally, as a consequence, the necessity to design and implement more adequate tools an instruments for urban and territorial management. On in all, this track call for the necessity of questioning the ‘meaning of existence’ of public policies in its relationship with the dimensions of contemporary urban complexity, in order to ensure a better quality of life and a more equal societal change.